Evaluación técnica y económica de la producción industrial de aceite de aguacate para uso en cosméticos. - Calderón Guzmán, Eveling Carolina. (2021)
This thesis project focuses on the feasibility of a technical and economic evaluation of avocado oil's industrial production for cosmetics use. For this purpose, identifying the extraction process of avocado oil and the characteristics and benefits in the cosmetics line was carried out. A market study was carried out among economically active women in Quito, where a sample of 138 women was surveyed. Information such as frequency and purchase intention was obtained to determine the demand scenarios. The information obtained was used in the technical and economic studies, where the plant's location and optimal size, the availability and cost of inputs, the identification and description of the process, and the legal and environmental requirements needed for the plant's operation were determined. The economic study was developed by taking all the information from previous sections, referring to direct and indirect costs, investments, interest rates, frequency, and purchase intention. In this technical and financial study, the NPV values were calculated: With $105.825,35 and an IRR of 25%, these values are indicators that the project has low investment risk. Also, It is higher than the nominal rate of the CFN, to develop the calculation of break-even point represents 45,40%, which allowed to visualize precisely the financial feasibility of this project to a term of 5 years with returns of capital inferior to the study, that is to say, that the viability of the project is verified looking for this way that a microenterprise enters with a novel product in the market.